Isolation of oleandrin, a cardiotonic glycoside from the leaves and stems of Nerium indicum Linee (Family Apocynaceae) - Bulandus, Rowena C.; Cruz, Ileana R. (Manila College of Pharmacy, University of the Philippines, 1989)
Oleandrin, a cardiotonic glycoside may be isolated from the leaves of Nerium indicum by refluxing with 65% ethanol.
Thin layer chromatography, paper chromatography and spectrophotometry were the methods used for quantitative and qualitative analysis. Adelfa, being a glycoside-yielding plant should be further studies for it is a possible source of a cheaper cardiotonic drug.
​Thesis (Bachelor of Science in Pharmacy)--University of the Philippines, March 1989.
Keywords: Oleander; Adelfa